Оптимізація системи автоматичногокеруваннякислотності та концентрації живильного розчину в гідропонних теплицях - Синявський, О. Ю.; Савченко, В. В. (Energy and Automation, 2017)
automatic control OPTIMIZATION of acidity and concentration of nutrient solution In hydroponic greenhouses A. Sinyavsky, V. Savchenko In hydroponic growing plants all the necessary minerals derived from plant nutrient solution, because the acidity (pH) and total concentration of the nutrient solution must be maintained at the optimum level throughout the growing season. Now in hydroponic greenhouses reusable nutrient solution adjusting its composition is performed on the basis of chemical analysis performed agrochemical laboratory. It does not allow for continuous monitoring of the changing parameters of the nutrient solution and its timely correction as the period between the analysis solution pH changes by 0.7-0.8 units, and concentration of mineral elements by 60-90%, although the concentration reject individual item 30% of its optimal value is a violation of plants absorption of other elements, resulting in lower yields and product quality. The aim - to optimize the automatic regulation of pH and concentration of the nutrient solution. Since the object management is characterized by large time delay and the need for separate components supply the nutrient solution in the required sequence: acid, concentrated solutions A and B, the water, it is best pulse law regulation. Switching regulators are based on positional adding pulse interrupters. Relay-switching regulator is connected in series nonlinear element simplest pulse elements and forming a circle. Using obtained transfer functions of elements of the automatic regulation of pH and concentration of nutrient solution developed algorithmic scheme for these systems. This system is nonlinear and discrete, characterized by lagging links. For the analysis of such systems must use the theory of nonlinear pulse of automatic control systems. The acidity and concentration of nutrient solution must be maintained at a level determined by cultural practices requirements. Quality Score by optimizing the system of automatic control of pH and concentration of nutrient solution taking the total deviation. This made it possible to determine the duration of pulses regulators for the automatic adjustment of acidity and concentration of nutrient solution for growing tomatoes and cucumbers, which are respectively 111 s, 153 s and 135 s. Quantization interval of time determined by the condition of absolute stability of the system. Quantization interval time 1140 s, which lies within the area defined stability parameter. As a result of the research of automatic control of pH and concentration of the nutrient solution in hydroponic greenhouses found that acidity nutrient solution deviation from the set value does not exceed 0.2 units. pH, and its conductivity - 0.02 S/m, which corresponds to agrotechnical requirements.